Boreal Bird Ecology, Management and Conservation - McNulty, Stacy A.; Glennon, Michale (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Northern forested landscapes are important habitats for many boreal birds. This Special Issue portrays the current state of knowledge on boreal bird diversity, ecology, management, and conservation. Humans have diverse impacts on boreal habitats worldwide, and knowledge of the avian community associated with these northern forests is key to conservation measures.